2013
DOI: 10.1155/2013/160123
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of 1,25-Dihydroxyvitamin D3on IL1β-Induced RANKL, OPG, TNFα, and IL-6 Expression in Human Rheumatoid Synoviocyte MH7A

Abstract: Receptor activator of nuclear factor κB ligand (RANKL) plays a crucial role in the bone erosion of rheumatoid arthritis (RA) by prompting osteoclastogenesis. Considering that 1,25(OH)2D3 has been suggested as a potent inducer of RANKL expression, it should clarify whether vitamin D supplement could result in RANKL overexpression and thereby facilitate excessive osteoclastogenesis and bone resorption in RA. Here, we investigated modulatory effect of 1,25(OH)2D3 on the expression of RANKL and its decoy receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 33 publications
5
43
0
Order By: Relevance
“…The binding capacity of OPG to RANKL is higher than that of RANK to RANKL, which competitively binds RANKL, thereby competitively inhibiting its binding to RANK (39). Consequently, OPG may inhibit the differentiation of osteoclasts (39). The present results suggested that LLDT-8 increases OPG gene expression, decreases RANKL gene expression, increases the ratio of OPG to RANKL and inhibits RANKL-induced NF-κB expression in the current rat model of CIA.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The binding capacity of OPG to RANKL is higher than that of RANK to RANKL, which competitively binds RANKL, thereby competitively inhibiting its binding to RANK (39). Consequently, OPG may inhibit the differentiation of osteoclasts (39). The present results suggested that LLDT-8 increases OPG gene expression, decreases RANKL gene expression, increases the ratio of OPG to RANKL and inhibits RANKL-induced NF-κB expression in the current rat model of CIA.…”
mentioning
confidence: 55%
“…RANK is located on the plasma membrane of osteoclast precursor cells, and the binding of RANKL to RANK promotes the differentiation and maturity of osteoclasts (38). The binding capacity of OPG to RANKL is higher than that of RANK to RANKL, which competitively binds RANKL, thereby competitively inhibiting its binding to RANK (39). Consequently, OPG may inhibit the differentiation of osteoclasts (39).…”
mentioning
confidence: 99%
“…87 In contrast to the reduction of RANKL expression by 1,25(OH) 2 D on leuko cytes, 58 the same metabolite was shown to increase RANKL expression in FLSs. 88 However, 1,25(OH) 2 D was also shown to enhance FLS-derived production of the RANKL decoy receptor osteoprotogerin (OPG) and increase the OPG:RANKL ratio. 88 Thus, 1,25(OH) 2 D might affect RA pathology by reducing osteoclast activation by FLSs.…”
Section: Fibroblastsmentioning
confidence: 99%
“…However, it is clear that 25(OH)D concentration decline after major surgery. [13][14][15] [16][17][18] Animal studies also indicate 1,25(OH) 2 D 3 and its analogs are effective antiinflammatories. [19][20][21] The mechanisms by which 1,25(OH) 2 D 3 reduces inflammation are multiple.…”
Section: Introductionmentioning
confidence: 99%